Behind the seams : women, fashion, and work in 19th-century France - Hiner, Susan (London : Bloomsbury Visual Arts, 2023)
"In this highly original book, Susan Hiner looks behind fashion's seams and focuses on the women fashion producers - both working- and middle-class -- who were key to shaping the French fashion economy. Behind the seams thus opens up the fields of both fashion and French cultural studies and explores new ways of understanding the 19th centry by demonstrating that these women's complex and contradictory roles as producers of luxury items left them exploited by an oppressive fashion system even as they served as influencers within it."-- Supplied by publisher.
Veiling women's work -- Fashion's fingers: immodest Modistes -- Fasion's voices: "Modistes des Lettres" -- Fashion's eyes: painting in the mirror -- Epilogue: Midinettes in motion.
Includes bibliographical references and index.
Keywords: 1800-1899.; Clothing trade -- History -- 19th century -- France; Clothing trade; Couturières (Créatrices de mode) -- Histoire -- 19e siècle -- France; Fashion -- History -- 19th century -- France; Fashion; Women fashion designers -- History -- 19th century -- France; Women fashion designers; France -- Histoire -- 19e siècle; France -- History -- 19th century; France; History